The Quality of Fresh Semen of Bulls at 5 0 C and 24 0 C With or Without Diluent - Kusumawati, Enike Dwi; Leondro, Henny (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
The aim of this study was to determine the quality of fresh sperm cattle at 5C and roomtemperature and used of diluent. The study was conducted at the Laboratory Animal HusbandryFaculty of Kanjuruhan University. Research material used was fresh sperm cattle that obtained fromthe Institute for Artificial Insemination (BIB) Singosari Malang. Decrease in motility and viabilitywithout extender were higher (P <0.01) compared with extender. Motility of spermatozoa decreasedto 10% at 12 hours without diluent. While the decrease in motility with diluent was 10% at 24 hours.It is also demonstrated motility of 0% at 96 hours without diluent while the semen with extenderhad 12.3 ± 2.16%. Also on the viability, the reduction reached 20% in diluent usage at 9 hours andwithout diluent at  3 hours. Decrease in motility and viability without diluent were higher (P <0.01) compared with diluent. Motility of spermatozoa decreased to 10% at 6 hours without diluent. Whilemotility with diluent decreased 6% at 6 hours. It is also demonstrated motility 1% at 42 hourswithout the diluent while the semen with diluent had 14.5 ± 0.53%. Also on the viability, on thereduction reached 20% in the use of diluent at 15 and 57 hours without diluent, 0% viability whilethe diluent at 57 hours was 31.171±0.37%. Abnormality in six hours without a diluent has shown adecrease of 20% whereas the diluent is still down 15%. The conclusion of this study is the quality ofspermatozoa in the storage temperature 5oC higher than storage at room temperature. The qualityof spermatozoa at 5oC temperature and room temperature with diluent is higher than withoutdiluent.Key Words: Sperm Quality, Time Storage, Temperature, Fresh Sperm, Diluent o